ASPEK SOSIAL GEISHA DALAM NAGASAKI BURA-BURA BUHSI - Endang Poerbowati (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
This article discusses the social aspects of geisha in Rei Nakanishi's novel entitled NagasakiBura-bura Bushi. The analysis shows that in carrying out her profession and their living in a socitey, ageisha is portrayed to have the nature of cooperation, competition, and dispute (conflict). In social groups,there are the groups of families and communities (rural and urban). In a society, there are norms ofmanners, habits, behavior patterns, and customs that must be maintained. In the sociology of women,women are not merely be seen in the relationship of marriage and family, but also are viewed in theirroles of their jobs and education. As a human being, geisha may have problems in their lives such ashaving a sense of love, anxiety, suffering, sorrow, and responsibility against themselves, others and Godor spirit or deity. The above mentioned can be traced through the interaction of the main characterAihachi and other characters.Keywords: geisha, aspek sosial, konflik